DOP32 Withdrawal of thiopurines in Crohn's disease treated with scheduled adalimumab maintenance: a prospective randomised clinical trial (DIAMOND2). (25th January 2019) - Hisamatsu, T; Kato, S; Kunisaki, R; Matsuura, M; Nagahori, M; Motoya, S; Esaki, M; Fukata, N; Inoue, S; Sugaya, T; Sakuraba, H; Hirai, F; et al.
Abstract: Background: The risk:benefit ratio of concomitant use of thiopurines with scheduled adalimumab (ADA) maintenance therapy for Crohn's disease is controversial. To study the influence of withdrawal of thiopurines in patients in remission with combination therapy in an open-label, randomised, controlled trial (DIAMOND2; UMIN UMIN000009596). Methods: Patients in corticosteroid-free clinical remission (CFCR) for ≥6 months with ADA (40 mg, s.c., every other week [e.o.w.]) scheduled maintenance combined with thiopurines were randomised to continue (Con) or discontinue (Dis) thiopurines, whereas all patients received scheduled ADA maintenance therapy for 52 weeks. The primary endpoint was the proportion of patients who had CFCR at Week 52. Secondary endpoints were mucosal healing, trough levels of ADA in serum, and safety. Results: Fifty patients were randomised to Con or Dis groups. The Crohn's Disease Activity Index ( p = 0.866), Simple Endoscopic Score for Crohn's Disease score ( p = 0.450), and serum C-reactive protein (CRP) level ( p = 0.694) at baseline were not significantly different between groups. CFCR prevalence at Week 52 was not significantly different between groups (log-rank, p = 0.704). Prevalence of endoscopic remission at Week 52 was not significantly different between groups ( p = 1.000). Trough levels of ADA in serum were not significantly different between groups ( p = 0.515). The proportion of patients with AAA positivity at Week 52 was not significantly different ( p = 0.437). No serious adverse effects were observed in either group. Conclusions: Continuation of thiopurines >6 months offers no clear benefit over scheduled ADA monotherapy. CFCR, endoscopic activity, and ADA trough level at Week 52 were not significantly different between groups (UMIN000009596).